2022
DOI: 10.3389/fcvm.2021.789392
|View full text |Cite
|
Sign up to set email alerts
|

Benefits and Pitfalls of the Perceval Sutureless Bioprosthesis

Abstract: Objective: To highlight the main target points covered by clinical studies on the Perceval sutureless valve for surgical aortic valve replacement (SAVR) and raise a point of discussion for further expansion of its use when compared with stented bioprostheses (SB) and transcatheter aortic valve replacement (TAVR).Methods: We reviewed clinical trials and retrospective studies published up to date and compared the outcomes in terms of mortality, myocardial infarction (MI) stroke, paravalvular leak (PVL), permanen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 54 publications
1
19
0
Order By: Relevance
“…2 The Perceval valve has comparable mortality and shorter intraoperative CPB times compared to insertion of conventional sutured aortic valves. 2,3 Furthermore, successful implantation of Perceval valves has been reported in cases of aortic valve IE. 4 We, however, report on the first known successful implantations of the Perceval sutureless bioprosthesis in the pulmonary position.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 The Perceval valve has comparable mortality and shorter intraoperative CPB times compared to insertion of conventional sutured aortic valves. 2,3 Furthermore, successful implantation of Perceval valves has been reported in cases of aortic valve IE. 4 We, however, report on the first known successful implantations of the Perceval sutureless bioprosthesis in the pulmonary position.…”
Section: Discussionmentioning
confidence: 99%
“…The Perceval sutureless prosthesis has proven to be a safe alternative to contemporary stented and non‐stented sutured valves when implanted in the aortic position 2 . The Perceval valve has comparable mortality and shorter intraoperative CPB times compared to insertion of conventional sutured aortic valves 2,3 . Furthermore, successful implantation of Perceval valves has been reported in cases of aortic valve IE 4 .…”
Section: Discussionmentioning
confidence: 99%
“…There are several practical implications when it comes to combining SAVR with RAT and the Perceval sutureless valve in patients with 2‐sinus BAV laterolateral phenotype: The surgical learning curve, the complexity of the procedure, and the recognition of anatomical structures with their morphology should be considered in the preprocedural planning, however, none of these aspects should discourage cardiac surgeons from adopting sternal‐sparing techniques to improve the delivery of care for patients, as also stated by other groups 7–11 …”
Section: Discussionmentioning
confidence: 99%
“…should be considered in the preprocedural planning, however, none of these aspects should discourage cardiac surgeons from adopting sternal-sparing techniques to improve the delivery of care for patients, as also stated by other groups. [7][8][9][10][11] 2. The advantages of SAVR with RAT approach can be followed by early ambulation and superior chest wall stability.…”
Section: Imaging and Electrocardiogram After Implantation Of Percevalmentioning
confidence: 99%
“…In addition, clinical studies have shown the noninferiority of the valves compared to the TAVR both in primary and redo aortic valve surgery. 5 Important characteristics of the rapid deployment valve include improved hemodynamics, a self-expanding radial force, usage in hostile roots, enhanced surgical and recovery speed, and enabling (MINV) cardiac surgery procedures. 6 However, many points deserve to be highlighted including the impact of paravalvular leak (PVL), stroke, permanent pacemaker implantation (PPI), structural valve deterioration (SVD), myocardial infarction (MI), endocarditis, long-term outcomes, MINV approach, hospital costs, and echocardiographic outcomes.…”
Section: Introductionmentioning
confidence: 99%